2014
DOI: 10.2967/jnumed.114.144840
|View full text |Cite
|
Sign up to set email alerts
|

89Zr-Bevacizumab PET Visualizes Heterogeneous Tracer Accumulation in Tumor Lesions of Renal Cell Carcinoma Patients and Differential Effects of Antiangiogenic Treatment

Abstract: No validated predictive biomarkers for antiangiogenic treatment of metastatic renal cell carcinoma (mRCC) exist. Tumor vascular endothelial growth factor A (VEGF-A) level may be useful. We determined tumor uptake of 89 Zr-bevacizumab, a VEGF-A-binding PET tracer, in mRCC patients before and during antiangiogenic treatment in a pilot study. Methods: Patients underwent 89 Zrbevacizumab PET scans at baseline and 2 and 6 wk after initiating either bevacizumab (10 mg/kg every 2 wk) with interferon-α (3-9 million IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 30 publications
(37 reference statements)
6
78
1
1
Order By: Relevance
“…89 Zr-labeled bevacizumab PET imaging may help in assessment of the inter-and intrapatient heterogeneity of drug biodistribution in vivo, thereby predicting the presence or absence of a response in patients subsequently treated with bevacizumab. Studies in both mice and adult patients confirmed that 89 Zr-bevacizumab PET imaging was feasible and able to reveal bevacizumab accumulation in VEGF-positive tumors (7,(12)(13)(14). In addition, in adult renal cancer tumors, 89 Zr-bevacizumab uptake was correlated with a response to bevacizumab treatment (13).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…89 Zr-labeled bevacizumab PET imaging may help in assessment of the inter-and intrapatient heterogeneity of drug biodistribution in vivo, thereby predicting the presence or absence of a response in patients subsequently treated with bevacizumab. Studies in both mice and adult patients confirmed that 89 Zr-bevacizumab PET imaging was feasible and able to reveal bevacizumab accumulation in VEGF-positive tumors (7,(12)(13)(14). In addition, in adult renal cancer tumors, 89 Zr-bevacizumab uptake was correlated with a response to bevacizumab treatment (13).…”
mentioning
confidence: 59%
“…In adults with renal cell carcinoma, it has been shown that a high level of baseline 89 Zr-bevacizumab uptake in tumors before treatment is positively associated with time to progression in bevacizumab-treated patients (13). A difficulty in performing such a study with DIPG patients is that current DIPG trials involve multiagent therapy regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the used artificial model, targeted intraperitoneal xenograft tumors stitched in a human colon specimen, demonstrates the practical feasibility of the proposed technique, but no statements can be made regarding specific tumor or adenoma accumulation in comparison to uptake in healthy human colon tissue. However, clinical studies evaluating the use of 89 Zr-labeled bevacizumab in breast and kidney cancer patients did not show aspecific accumulation of the tracer in the colon (32). Also, the significantly higher VEGF-A expression in colorectal adenomas than in adjacent normal tissue implies that bevacizumab-800CW could be a promising tracer from a diagnostic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…1B) (21-24). They clearly showed that a drug targeting a growth factor in the microenvironment can be visualized using protein tracer doses as low as 5 mg. For RCCs, 89 Zr-bevacizumab PET showed heterogeneous tracer accumulation in tumor lesions (21). Serial 89 Zr-bevacizumab PET showed that a therapeutic dose of bevacizumab and interferon-a reduced tracer uptake.…”
Section: Use Of Theranostics In Clinical Decision Makingmentioning
confidence: 99%